Association of intermittency with electron heating in the near-Sun solar wind. Issue 1 (15th November 2022) - Phillips, C; Bandyopadhyay, R; McComas, D J; Bale, S D
ABSTRACT: Several studies in the near-Earth environment show that intermittent structures are important sites of energy dissipation and particle energization. Recent Parker Solar Probe (PSP) data, sampled in the near-Sun environment, have shown that proton heating is concentrated near coherent structures, suggesting local heating of protons by turbulent cascade in this region. However, whether electrons exhibit similar behaviour in the near-Sun environment is not clear. Here, we address this question using PSP data collected near the Sun during the first seven orbits. We use the partial variance of increments (PVI) technique to identify coherent structures. We find that electron temperature is preferentially enhanced near strong discontinuities. Our results provide strong support for the inhomogeneous heating of electrons in the 'young' solar wind associated with the dissipation of turbulent fluctuations near intermittent structures.